Degradation and mechanism of 2, 4-dichlorophenoxyacetic acid (2, 4-D) by thermally activated persulfate oxidation. (December 2018) - Cai, Jingju; Zhou, Minghua; Yang, Weilu; Pan, Yuwei; Lu, Xiaoye; Serrano, Karine Groenen
Abstract: The chlorinated phenoxy herbicide of 2, 4-dichlorophenoxyacetic acid (2, 4-D) was oxidized by thermally activated persulfate (TAP). This herbicide was studied for different persulfate dosages (0.97–7.29 g L −1 ), for varying initial pH levels (3–12) and temperatures (25–70 °C). Compared with Fe 2+ /PS, TAP could achieve a higher total organic carbon (TOC) removal under wider pH ranges of 3–12. Increasing the mole ratio of PS to 2, 4-D favored for the decay of 2, 4-D and the best performance was achieved at the ratio of 50. The 2, 4-D degradation rate constant highly depended on the initial pH and temperature, in accordance with the Arrhenius model, with an apparent activation energy of 135.24 kJ mol −1 . The study of scavenging radicals and the EPR confirmed the presence of both SO4 − and OH. However, SO4 − was the predominant oxidation radical for 2, 4-D decay. The presence of both Cl − and CO3 2− inhibited the degradation of 2, 4-D, whereas the effect of NO3 − could be negligible. Verified by GC/MS, HPLC and ion chromatography, a possible degradation mechanism was proposed. Highlights: Thermally activated persulfate (TAP) could effectively degrade 2, 4-D compared with Fe 2+ /PS. TAP had higher TOC removal, longer radical duration time and wider pH applicability than Fe 2+ /PS. A possible degradation pathway for 2, 4-D was proposed. TAP was a promising method for removal of herbicide.